EAHP Survey 2010 on hospital pharmacy in Europe: Part 6. Education and research. Issue 4 (22nd April 2013) - Frontini, Roberto; Miharija-Gala, Tajda; Sykora, Juraj
Abstract : Hospital pharmacies in Europe are very involved in the education of pharmacy and medical students as well as in the training of technicians and nurses. The picture is similar regarding internal continuing education (which includes education on patient safety), but full or partial reimbursement of expenses is rare. Hospital pharmacists in Europe are involved in clinical research (mostly for clinical trials), drug evaluation and epidemiology studies. Oncology and general teaching hospitals are the most active in this field with general non-teaching hospitals carrying out less research.